The determinants that influence credit card usage intentions among students in UiTM Malacca City Campus / Rozhazrin Ayu Bolhi - Bolhi, Rozhazrin Ayu (2012)
Coupled with the liberalization in financial sector and the new era of cashless world shown that most people are more prefer to use credit card. Recently, the trends of using credit card have spread through all country over the world and social class as well as in Malaysia. However, some of the individuals tend to misuse this service and lead to the issue of bankruptcy. Therefore, by identify what factors influences credit cards usage intentions may helps the authority and the government to find out the solutions as to cope with this issue. This study was carried out to determinethe determinants of credit card usage intention among student in UiTM Malacca city Campus. A total of one hundred respondents, which is business students in UiTM Malacca City Campus were randomly selected to be respondents of the study. A set of questionnaires was administered to gain primary data from the respondents about credit card usage intentions. The overall findings of the study indicate the determinants which is financial status and product and services offered influences the credit card usage intentions among the students. In conclusion, some recommendations need to apply in order to gain better result for the future research and might be usefull for other parties.